What are the challenges of extending ERP to the shop floor? A study at Aero Engine Controls - Kemp, Fiona (2013)
Many manufacturing organisations do not use their ERP system to manage shop floor activity, therefore this research study addresses the question of “What are the challenges of extending ERP to the shop floor?”. A twofold approach has been used to address this question. Firstly, the literature on information architecture, ERP systems and MES is reviewed to understand relevant previous research that has been conducted. Secondly, key stakeholders, users and operators of different combinations of systems in plants manufacturing complex engineering products, are interviewed to obtain different perspectives on the issues raised in integrating ERP and MES. A discussion of findings from the literature and from the interviews is then presented. The study concludes with recommendations for implementation of new information architecture within a manufacturing organisation.